PERBANDINGAN PENGGUNAAN KAMPAS DAN PLAT KOPLING HONDA TIGER DENGAN KAMPAS DAN PLAT KOPLING ORIGINAL HONDA GL 100 TERHADAP PERFORMA MESIN SEPEDA MOTOR HONDA TIGER - Irfan Zidni1, Muhammad; Budiyono, Budiyono; Prasetyo, Imam (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
From various sources of problems regarding the performance of the Honda Tiger motorcycle engine when using the standard lining and clutch plate, the engine performance is less powerful, while various sources suggest that the best performance is produced from the Honda Tiger engine by using components such as the canvas and clutch plate of the Honda GL 100 motorcycle. The objective to be achieved in this final project is to determine the difference in power and torque produced by the engine using standard honda tiger pads and clutch plates and honda gl 100 clutch plates and plates, this final project was carried out using the test data collection method from daynote , using a dynamometer. The results of the best engine performance testing on the use of the Honda gl 100 pad and clutch plate on the Honda Tiger engine, produced a maximum power value of 16.0 HP at 7250 RPM engine speed and also produced a maximum torque value of 17.32 Nm at 5250 RPM engine speed, This is because of the influence of the difference in the clutch plate of the Honda GL 100 which is circular in shape with dots so that the grip on the clutch lining becomes tighter and makes the performance of power and torque better.Keywords : Canvas, Clutch Plate, Power, Torqu